GE_GERICHTE C/24357/2013 vom 26. August 2015 - GE Cour de justice (2015)
INDEMNITÉ(EN GÉNÉRAL); FRAIS DE VOYAGE | CPC.34; CPC.147; CPC.148; CPC.149; CPC.247.2.b.2; CPC.160.1; CPC.317.1; CO.327a.1; CCT.18.a.3; CO.339.1